The ecology and management of the large carnivore guild on Shamwari Game Reserve, Eastern Cape,Ecology and management of the large carnivore guild on Shamwari Game Reserve, Eastern Cape, South Africa - O'Brien, John William (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2013)
Shamwari Game Reserve was the first enclosed conservation area in the Eastern Cape Province of South Africa to reintroduce free ranging lions, cheetahs, leopards and wild dogs back into their historic range. At that time (2000 "“ 2001), little information was available on the ecology and behaviour of these predators in the habitats of the Eastern Cape, and management decisions were based on assumptions and unfounded comparisons with extant populations but from quite different habitats. The aim of this study was therefore to obtain a better understanding of the feeding ecology and space use of the predator guild, and the carrying capacity of Shamwari Game Reserve to enable more informed management decisions. In addition, the reserve is a photographic based tourism venture and understanding both the ecological and financial sustainability of the predator guild was important. The diets of the predators were similar to those reported in other studies; larger predators killed a greater range of prey species than did smaller predators and a small number of prey species made up the majority of the kills. The larger predators had a higher mean kill mass than the smaller species and prey selection was influenced by prey size, prey abundance and prey habitat preference, and risk associated with hunting the species. Diet was flexible and responded to natural and management induced changes in prey abundance. There was a considerable overlap in space use by the lions, cheetahs and leopards with their core areas being centred on and around the Bushmans River. Space use was driven by resource distribution and landscape attributes, and by the presence of other predators of the same or different species. The long term viability of wild dog within the reserve was explored and the results confirmed that there was neither the required space nor the ecological processes and the wild dogs were removed from the reserve. A carrying capacity of the reserve for the predator guild was determined using the Maximum Sustainable Yield method to assess the potential prey species off take and a resultant density of 3.3 to 6.6 lion female equivalent units per 10 000 ha was established. The natural carrying capacity of the reserve with respect to predators will not sustain the tourism objectives and consequently prey supplementation was necessary to maintain predator density at levels high enough to sustain tourism. Under these conditions the large predator guild is still sustainable financially although careful, responsible management is needed to provide ecological sustainability.
Keywords: Cheetah -- Behavior -- South Africa -- Shamwari Game Reserve; Shamwari Game Reserve (South Africa); Carnivora -- South Africa -- Shamwari Game Reserve; Wildlife conservation -- South Africa -- Shamwari Game Reserve; Game reserves -- Management -- South Africa -- Shamwari Game Reserve; Lion -- Behavior -- South Africa -- Shamwari Game Reserve; Lion -- Ecology -- South Africa -- Shamwari Game Reserve; African wild dog -- Ecology -- South Africa -- Shamwari Game Reserve; Cheetah -- Ecology -- South Africa -- Shamwari Game Reserve; Lion -- Food -- South Africa -- Shamwari Game Reserve; Lion -- Food -- South Africa -- Shamwari Game Reserve; Cheetah -- Food -- South Africa -- Shamwari Game Reserve; African wild dog -- Behavior -- South Africa -- Shamwari Game Reserve; African wild dog -- Food -- South Africa -- Shamwari Game Reserve; Leopard -- Behavior -- South Africa -- Shamwari Game Reserve; Leopard -- Ecology -- South Africa -- Shamwari Game Reserve; Leopard -- Food --South Africa -- Shamwari Game Reserve